Profile of recipients of holistic health counselling in a psychiatric OPD in South India. (May 2021) - Gandhi, Sailaxmi; Mohanty, Krutideepa; Sahu, Maya; Naik, Shalini S; Pahuja, Erika; Gunasekaran, Durai Murukan; Prasad, M. Krishna
Background of the study: Persons with mental illness (PwMI) are prone to weight gain as a side effect of antipsychotics. Health counselling on diet, physical activity, medication adherence, expressed emotions and technology use, by health professionals, can help in managing these side-effects. Aim: The aim of this study was to identify the pre-counselling profile of the subjects such as body mass index (BMI), diet, physical activity, medication adherence, expressed emotions and technology use among PwMI; to attend the Holistic Health Clinic as part of follow-up services in the psychiatry Outpatient Department (OPD) as well as to find correlation and association between the study variables. Methods: The study involved a cross-sectional descriptive design based on convenience sampling. The sample consists of 56 patients who are receiving antipsychotics under symptom control (self-reported) and were overweight. Data were collected with a patient assessment proforma and analysed using SPSS-22. Results: The patients referred to the holistic health counselling (HHC) had abnormal weight and BMI. The mean and SD of weight was 74.48 ± 14.07 and BMI 29.51 ± 5.15. All the participants received counselling on diet, 87.5% on physical activity, 62.5% on sleep hygiene, 55.4% on medication adherence, 8.9% on family emotional climate and only 5.4% on healthy use of technology. Weight has shown significant relation with gender (male = 80.84 ± 17.71, female = 71.09 ± 10.52, t = −2.52, p = .015) and near to significant relationship (χ 2 = 7.685, p = .053) with educational status. Conclusion: Patients receiving second-generation antipsychotics (SGA) have lesser extra pyramidal side-effects; however, they are more prone to gain weight. Proper screening and counselling during the follow-up visit in the outpatient setting can help in identification, prevention and management of the obesity-related metabolic syndrome and cardiovascular disease (CVD), and motivate them to adopt healthy behaviours.